Biomechanical influence of T1 tilt alteration on adjacent segments after anterior cervical fusion - Wei, Wei; Du, Xianping; Li, Na; Liao, Yunjie; Li, Lifeng; Peng, Song; Wang, Wei; Rong, Pengfei; Liu, Yin (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Anterior cervical fusion (ACF) has become a standard treatment approach to effectively alleviate symptoms in patients with cervical spondylotic myelopathy and radiculopathy. However, alteration of cervical sagittal alignment may accelerate degeneration at segments adjacent to the fusion and thereby compromise the surgical outcome. It remains unknown whether changes in T1 tilt, an important parameter of cervical sagittal alignment, may cause redistribution of biomechanical loading on adjacent segments after ACF surgery. Objective: The objective was to examine the effects of T1 tilt angles on biomechanical responses (i.e.range of motion (ROM) and intradiscal VonMises stress) of the cervical spine before and after ACF. Methods: C2–T1 FE models for pre- and postoperative C4–C6 fusion were constructed on the basis of our previous work. Varying T1 tilts of −10°, −5°, 0°, 5°, and 10° were modeled with an imposed flexion–extension rotation at the T1 inferior endplate for the C2–T1 models. The flexion–extension ROM and intradiscal VonMises stress of functional spinal units were compared between the pre- and postoperative C2–T1 FE models of different T1 tilts. Results: The spinal segments adjacent to ACF demonstrated higher ROM ratios after the operation regardless of T1 tilt. The segmental ROM ratio distribution was influenced as T1 tilt varied and loading conditions, which were more obvious during displacement-control loading of extension. Regardless of T1 tilt, intradiscal VonMises stress was greatly increased at the adjacent segments after the operation. As T1 tilt increased, intradiscal stress at C3–C4 decreased under 30° flexion and increased under 15° extension. The contrary trend was observed at the C6–C7 segment, where the intradiscal stress increased with the increasing T1 tilt under 30° flexion and decreased under 15° extension. Conclusion: T1 tilt change may change biomechanical loadings of cervical spine segments, especially of the adjacent segments after ACF. Extension may be more susceptible to T1 tilt change.